2014
DOI: 10.1053/j.ackd.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Disease Reversal in Focal and Segmental Glomerulosclerosis

Abstract: It is well known that progression of chronic kidney disease can be ameliorated or stabilized by different interventions, but more and more studies indicate that it can even be reversed. Most data suggest that current therapy, especially renin angiotensin system inhibition alone, is not sufficient to initiate and maintain long term regression of glomerular structural injury. In this article, we review the potential reversal of glomerulosclerosis and evidence from both human and animal studies. We discuss mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…This result is consistent with the presence of hypercellularity and enlargement of glomeruli that precede glomerulosclerosis and kidney dysfunction. Similar studies in mice with more advanced disease stages deserve to be carried out to decipher the sequential molecular events leading to glomerulosclerosis, but our results suggest that TGFβ overproduction and its consequences are secondary events following LC-induced proliferation This result is in accordance with studies of human diseases, including diabetic nephropathy (44,45) which showed that glomerulosclerosis at early stages can be reversed with efficient treatment, although this process in humans can take several years. In mouse models, however, the reversibility was demonstrated after short term treatment in diabetic nephropathy (46,47) or hypertension-related glomerulosclerosis (48).…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with the presence of hypercellularity and enlargement of glomeruli that precede glomerulosclerosis and kidney dysfunction. Similar studies in mice with more advanced disease stages deserve to be carried out to decipher the sequential molecular events leading to glomerulosclerosis, but our results suggest that TGFβ overproduction and its consequences are secondary events following LC-induced proliferation This result is in accordance with studies of human diseases, including diabetic nephropathy (44,45) which showed that glomerulosclerosis at early stages can be reversed with efficient treatment, although this process in humans can take several years. In mouse models, however, the reversibility was demonstrated after short term treatment in diabetic nephropathy (46,47) or hypertension-related glomerulosclerosis (48).…”
Section: Discussionsupporting
confidence: 89%
“…The histopathological improvement is in accordance as in [11] which showed that administration of ACE inhibitors can improve the histopathology of glomerulosclerosis by increasing the amount of plasmin by decreasing the expression of PAI-1 (Plasminogen Activator Inhibitor-1) which occurs due to a decrease in angiotensin II. The increase in plasmin levels will increase degradation of the extracellular matrix and lyse fibrin (matrix remodeling).…”
Section: Fig 2 Diastolic Blood Pressure Linear Test Graphsupporting
confidence: 85%
“…Glucocorticoids which interact with glucocorticoid receptors in smooth and endothelial blood vessels which will increase the activation of AT-1 receptors. Angiotensin II which binds to AT-1 and At-2 will induce aldosterone synthesis which will increase in plasma volume and blood pressure [9]- [11].…”
Section: Fig 1 Systolic Blood Pressure Linear Test Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerulosclerosis (GS) is an inflammatory disease. The pathogenic mechanisms include dysregulation of lipid metabolism, production of inflammatory mediators, mesangial cell (MC) proliferation, intra‐ and extracellular lipid accumulation, and matrix production . However, the mechanisms are still not fully elucidated.…”
mentioning
confidence: 99%